Toward a Unified Account of the Intentionality of Mind: The Case of Hervaeus Natalis - Amerini, Fabrizio (American catholic philosophical quarterly, 2024)
Our mental states are considered intentional in that they express a directedness toward something. Mental states include acts of thought and will, acts of consciousness, emotions, and possibly acts of sense perception. Did any medieval philosopher give a unified account of all these acts? In the Middle Ages, no author explicitly offers such an account. There is however one author, the Dominican Hervaeus Natalis (†1323), who explains intentionality in a way that allows us to extract from his texts the unified account we are searching for. The key to obtaining this account is to approach intentionality from the side of the thing that is intended. For if we are in relation to things, things, too, are in relation to us. Specifically, Hervaeus holds that intentionality designates a kind of relation, not however the relation ensuing from our directedness toward things (as we are accustomed to understanding it today), but the relation that things bear on us. This is a primitive and radical condition that specifically endows every mental state with intentional character.